Lung Gene Expression Analysis (LGEA): an integrative web portal for comprehensive gene expression data analysis in lung development. Issue 5 (9th January 2017) - Du, Yina; Kitzmiller, Joseph A; Sridharan, Anusha; Perl, Anne K; Bridges, James P; Misra, Ravi S; Pryhuber, Gloria S; Mariani, Thomas J; Bhattacharya, Soumyaroop; Guo, Minzhe; Potter, S Steven; Dexheimer, Phillip; et al.
Abstract : 'LungGENS', our previously developed web tool for mapping single-cell gene expression in the developing lung, has been well received by the pulmonary research community. With continued support from the 'LungMAP' consortium, we extended the scope of the LungGENS database to accommodate transcriptomics data from pulmonary tissues and cells from human and mouse at different stages of lung development. Lung Gene Expression Analysis (LGEA) web portal is an extended version of LungGENS useful for the analysis, display and interpretation of gene expression patterns obtained from single cells, sorted cell populations and whole lung tissues. The LGEA web portal is freely available at http://research.cchmc.org/pbge/lunggens/mainportal.html .